Deciphering cumulative fault slip vectors from fold scarps: Relationships between long‐term and coseismic deformations in central Western Taiwan. Issue 7 (14th July 2014) - Le Béon, Maryline; Suppe, John; Jaiswal, Manoj K.; Chen, Yue‐Gau; Ustaszewski, Michaela E.
Abstract We document the 30 ka cumulative slip history and long‐term slip vector azimuth on the northern Chelungpu fault based on a series of fault‐bend folded alluvial terraces and draw quantitative relationships between geological structure, deformation observed from the geomorphology, and coseismic displacements during the 1999 Mw = 7.6 Chi‐Chi earthquake. In our study area, three main terrace levels show progressive folding by kink band migration in relation to the underlying fault geometry, forming a main N‐S fold scarp up to ~193 m high and secondary E‐W scarps. Detailed analysis using 5 m resolution digital elevation model allows us to characterize the scarp morphology and quantify the deformation parameters, namely, terrace heights, fold scarp relief, and fold limb width and slope angle. The 3‐D deformation of the highest terrace, dated by optically stimulated luminescence at 30.2 ± 4.0 ka, enables to simultaneously determine amplitude and azimuth of the long‐term slip vector based on scarp relief. The long‐term slip vector, oriented N338° ± 6°, is found to parallel the Chi‐Chi coseismic displacements in this area. Cumulative slip and dating results yield a constant slip rate of 17.7 ± 2.2 mm/a in the direction N338° ± 6°. Late Quaternary shortening rates observed at four sites vary along strike in a similar way to Chi‐Chi coseismic displacements. Together with the collinearity of long‐term and coseismic slip vectors at our study site, this suggests that Chi‐Chi earthquake is a characteristic earthquake for the Chelungpu thrust with recurrence interval ~470 years. We also discuss implications for the regional and long‐term distribution of shortening in the central Western Foothills.